Adsorptive removal of hazardous crystal violet dye form aqueous solution using Rhizophora mucronata stem-barks: Equilibrium and kinetics studies - Chrispine M. Oloo; John M. Onyari; Wycliffe C. Wanyonyi; John N. Wabomba; Veronica M. Muinde (Environmental Chemistry and Ecotoxicology, 2020)
Adsorption of crystal violet (CV) dye from aqueous solution using dried bark powder of mangrove species Rhizophora mucronata was studied. Characterization of adsorbent was done using FTIR and SEM. Batch experiment was carried out to examine the viability of using mangrove bark for adsorption of CV dye from aqueous solutions under different process conditions. The result revealed that removal of CV increased with contact time, adsorbent dose, initial dye concentration and decreased with increased particle size and ionic strength. pH 7 was the optimum pH for CV dye removal. The adsorption equilibrium for CV dye by Rhizophora mucronata stem-bark was attained within 60 min with removal efficacy of up to 99.8%. Pseudo-second-order kinetic model was best used to describe sorption kinetics while Freundlich isotherm model was appropriate for describing adsorption isotherm. The results demonstrated that in their raw unmodified form, Rhizophora mucronata stem-bark is an effective for dyes removal from industrial effluents.